Atypical spindle cell/pleomorphic lipomatous tumor: A clinicopathologic, immunohistochemical, and molecular study of 20 cases. Issue 10 (9th September 2018) - Bahadır, Burak; Behzatoğlu, Kemal; Hacıhasanoğlu, Ezgi; Koca, Sevim Baykal; Sığırcı, Buket Bambul; Tokat, Fatma
Abstract : Lipomatous tumors accompanied by spindle cell component are not frequently encountered, and there are still problems regarding their differential diagnosis, nature, and nomenclature. To contribute to ongoing efforts, we present the clinical, histologic, and immunohistochemical characteristics of 20 cases of spindle cell lipomatous tumors with atypical features that may also be called atypical spindle cell/pleomorphic lipomatous tumors. Of the patients, 13 were men and 7 were women with an average age of 57.5 years. The most commonly affected site was the extremities. Twelve tumors arose in the subcutaneous tissue, while eight cases were located in the deep soft tissues. Tumor margins were often ill‐defined with invasion into the surrounding tissues. Microscopic examination revealed a wide spectrum of histologic features. All cases consisted of poorly marginated proliferation of mildly atypical spindle cells set in a fibrous or myxoid stroma with a variable amount of adipocytic component showing variation in adipocyte size and scattered nuclear atypia and frequent univacuolated or multivacuolated lipoblasts. Tumor cellularity and the relative proportion of the components were highly variable. One tumor showed morphologic features evocative of dedifferentiation and another one exhibited histological features resembling pleomorphic liposarcoma. None of the patients had recurrence or metastasis at follow‐up.